(untitled) (Asian Journal of Social Science Studies, 2022)
2020 is a year of massive outbreaks of COVID-19, which has a huge impact on the lives of people around the world. In 2020, China Daily, a major mainstream English-language newspaper in China, provided detailed coverage of the outbreak facts in countries around the whole world. In these reports, both subjects of discourse from China and from abroad spoke out, expressing China to the world and conveying voices from the world to China. The reports about the COVID-19 in China Daily were taken as the research objects, and the relevant reports among them were manually identified and screened to build a corpus for discourse subject analysis. This study focuses the analysis on the discourse subjects as the Other, such as foreigners in China and voices from the international community. By analyzing the voices of the other in the text, readers can understand the image China has created in the international community and the responsibility and accountability China embodies as the largest developing country. By selecting and analyzing typical discourse subjects as the Other from the self-constructed corpus, this study aims to analyze the international image portrayed by China and to investigate the important role of different discourse subjects in news reporting.